Quality indicators in end-of-life care - Ostgathe, Christoph; Voltz, Raymond (Current opinion in supportive and palliative care, 2010)
Purpose of review As quality in end-of-life care for the seriously ill and dying patient and his relatives is the central aim of palliative care, the development of clinically relevant quality indicators is essential. To get an insight into the most recent advances concerning quality indicators in end-of-life care, a literature review has been performed. Recent findings The definitions of end-of-life and palliative care differ widely. However, comprehensive domains of end-of-life care have been developed and translated into indicators to monitor quality in end-of-life care, mostly on national levels. A substantial number of indicators exist derived using an inhomogeneous methodological quality. Gaps are described mainly for the spiritual, religious, existential and cultural aspects of care. Summary In most domains of care the existing indicators have to be specified methodologically. Missing domains mainly concerned with spiritual, religious, existential and cultural aspects have to be focused on to develop meaningful indicators. Additionally the initiatives working on national levels have to collaborate to bring together all their valuable information. Above that the patients and families insight, on what they perceive as quality, should be listened to more intensely. Copyright © Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2025-10-27
Keywords: End-of-life care; Palliative care; Quality indicator